2011
DOI: 10.3892/ijo.2011.1047
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of EGR-1 modulates the activity of NF-κB and AP-1 in prostate carcinoma PC-3 and LNCaP cell lines

Abstract: Abstract. To address elements that might uniquely characterize EGR-1 mediated signaling, the expression of two transcription factors, namely, nuclear factor kappa B (NF-κB) and activator protein-1 (AP-1) were studied. PC-3 and LNCaP prostate carcinoma cell lines were transiently transfected with wildtype Egr-1 expression plasmid (pCMV-Egr-1) and treated with cisplatin and TPA. Overexpression of EGR-1 was found to induce nuclear expression of both, NF-κB and AP1. However, the intensity of the induced AP-1 and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 35 publications
4
27
0
Order By: Relevance
“…Our results show that indeed, without an external source of Egr-1, constitutive activation of NF-κB and AP-1 is associated with the expression of Egr-1, as knockdown of Egr-1 expression caused a significant inhibition of NF-κB and AP-1 activity and reduction in p21 and cIAP2 mRNA expression. This corroborates our previous studies that have suggested that forced expression of Egr-1 in PC-3 and LNCaP cells causes constitutive activation of NF-κB and AP-1 (38). The external stimulation of Egr-1 may be advantageous to proliferation, survival, motility and invasion, and resistance to cytotoxic drugs, when surviving in an ectopic environment, such as during seeding and growth in distant organs, such as the bone and lungs.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Our results show that indeed, without an external source of Egr-1, constitutive activation of NF-κB and AP-1 is associated with the expression of Egr-1, as knockdown of Egr-1 expression caused a significant inhibition of NF-κB and AP-1 activity and reduction in p21 and cIAP2 mRNA expression. This corroborates our previous studies that have suggested that forced expression of Egr-1 in PC-3 and LNCaP cells causes constitutive activation of NF-κB and AP-1 (38). The external stimulation of Egr-1 may be advantageous to proliferation, survival, motility and invasion, and resistance to cytotoxic drugs, when surviving in an ectopic environment, such as during seeding and growth in distant organs, such as the bone and lungs.…”
Section: Discussionsupporting
confidence: 79%
“…The phenotype of this inhibition is seen as the cell cycle arrest at the G1 to S-phase transition. This study complements and extends our previous study (38) in which a 5-10-fold increase in Egr-1 mRNA, NF-κB and AP-1 and protein levels in cell culture studies were observed. This compares to our finding that siRNA mediated silencing resulted in >98% reduction in Egr-1 mRNA and 91% reduction in Egr-1 protein in vitro, which led to dramatic changes in the cellular phenotype.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Membranes were incubated with SAP/JNK, p38 or ERK-1/2 antibody (dilution 1:1,000) and PP4 antibody (dilution 1:1,000) (Santa Cruz Biotechnology). Primary incubation was followed by incubations with HRP-conjugated secondary antibody (1:2,000; NEB), and detection was made with super signal chemiluminescent substrate (31)(32)(33)(34).…”
Section: Plasmid Construction and Preparation Of Nuclear Extractsmentioning
confidence: 99%